STUDYING AND ANALYZING THE COMPOSITION OF THE MINERAL FROM THE “DAUTOSH” DEPOSIT USING THE LASER DIFFRACTION METHOD (Scientific journal of the Fergana State University, 2026)
The purpose of this study is to investigate the composition of a mineral sample from the “Dautosh” deposit located in southern Uzbekistan and to evaluate its potential as a source of mineral fertilizers. The research employed the laser diffraction method to determine particle size, volume distribution, and elemental composition. The findings revealed that the average particle size is 5.61 μm, with manganese (75.02%), calcium (12.53%), iron (5.81%), and silicon (5.32%) as the primary components. The environmental safety of the mineral was also assessed. It is concluded that the use of this mineral for producing manganese-based fertilizers could contribute to the establishment of a new chemical industry sector in Uzbekistan and enhance agricultural productivity.